Comparison of game data between halves and quarters in division I women`s lacrosse - Thornton, A. R.; Figueroa, Y.; Davis, P.; Bunn, J. A. (Journal of Science in Sport and Exercise, 2025)
Purpose The purpose of this study was to compare in-game external load demands from the previous game format (two, 30-min halves) to the new format (four, 15-min quarters) in collegiate women`s lacrosse.